Use of modern financial instruments to attract investments into the construction industry - MAKSIUTA, Anton (Ways to Improve Construction Efficiency, 2025)
The construction sector traditionally occupies a key position in the economic system of the state, as under an efficient and balanced socio-economic policy it can serve as a powerful driver of economic growth. Construction plays an essential role in achieving strategic societal goals by modernizing infrastructure, improving the quality of the built environment, and stimulating business development. Through the implementation of construction and investment projects at national, regional, and local levels, the sector contributes to the creation of new production facilities, housing, social institutions, and transport networks. In the current context, Ukraine’s progress toward the economic standards of leading global economies is directly linked to the intensification of investment activity and the large-scale mobilization of financial resources to modernize and renew fixed assets. Modern financial instruments capable of attracting domestic and foreign investments – such as project financing, infrastructure bonds, private equity funds, and public-private partnerships – are becoming increasingly important. Expanding capital investment in new construction, reconstruction, and technological modernization must go hand in hand with strengthening the production capacity and material-technical base of the construction industry. A separate focus is the current state of the construction sector during the full-scale war. Military aggression has caused massive destruction of residential, industrial, transport, and social infrastructure. This situation has simultaneously created an unprecedented demand for reconstruction and recovery projects, requiring rapid investment mobilization and the use of flexible, innovative financing mechanisms. Despite heightened risks, wartime conditions stimulate new forms of cooperation, including public-private partnerships, the involvement of international donor and investment funds, and the development of war-risk insurance tools that enable the implementation of both urgent repair works and long-term reconstruction initiatives. Therefore, examining the application of modern financial instruments to attract investment into the construction industry – especially under wartime conditions – is highly relevant. Such research provides insights into effective recovery mechanisms, investment enhancement strategies, and pathways to strengthening the sector’s resilience and supporting sustainable economic development.